(untitled) (Bangladesh Journal of Medical Microbiology, 2013)
Bacterial pathogens were isolated from pus, wound swab, urine, blood and throat swab. A total of 300 samples were collected from Sir Salimullah Medical College & Mitford Hospital (SSMC & MH), BIRDEM and National Medical College (NMCH) and processed following standard microbiological methods. Antibiotic susceptibility testing were performed on pure culture isolates by employing Kirby-Bauer disc-diffusion method for the commonly used antibiotics. 326 (93.33%) bacterial pathogens were isolated from 300 patients. Single bacterial pathogen was present in 78% cases and mixed bacterial pathogens were in 15.40% cases. Staphylococcus aureus was the predominant species (38.66%) followed by Escherichia coli (38%), Pseudomonas spp. (13.33%), Proteus spp. (8.33%), CoNS (7.66%), Serratia spp (2.85%), Klebsiella spp. (2.00%) and Acinetobacter spp. (0.97%). Resistance rate towards amoxicillin, ciprofloxacin, co-trimoxazole and ceftriaxone were high among both Gram-positive and Gram-negative isolates. However, both groups showed good susceptibility to gentamicin and levofloxacin. S. aureus and CoNS showed 100% sensitivity to vancomycin and all isolated Gram negative organisms showed 98-100% sensitivity to imipenem.These results indicate that gentamicin and levofloxacin may be convenient alternative antimicrobial agent for both Gram-positive and Gram-negative bacteria and vancomycin for Gram positive and imipenem for Gram negative bacteria as well. DOI: http://dx.doi.org/10.3329/bjmm.v7i2.19327 Bangladesh J Med Microbiol 2013; 07(02): 13-16